2019
DOI: 10.1016/j.molp.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Auxin-Regulated Protein ZmAuxRP1 Coordinates the Balance between Root Growth and Stalk Rot Disease Resistance in Maize

Abstract: To optimize fitness, plants must efficiently allocate their resources between growth and defense. Although phytohormone crosstalk has emerged as a major player in balancing growth and defense, the genetic basis by which plants manage this balance remains elusive. We previously identified a quantitative diseaseresistance locus, qRfg2, in maize (Zea mays) that protects against the fungal disease Gibberella stalk rot. Here, through map-based cloning, we demonstrate that the causal gene at qRfg2 is ZmAuxRP1, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 40 publications
5
70
0
Order By: Relevance
“…Furthermore, lots of DEGs were markedly enriched into plant hormone signal transduction pathway. Consistently, it has been reported that auxin [74,75], cytokinins [76,77], ethylene [75,[78][79][80], gibberellin [81], abscisic acid [75,82,83], brassinosteroids [80], salicylic acid [75,78,84], jasmonic acid [75,78,[84][85][86], strigolactones [87] can actively participate in disease response. Among them, salicylic acid signal transduction and jasmonic acid/ethylene signal transduction are considered as the most common plant hormone signal transduction pathways in response to biological or abiotic stress.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, lots of DEGs were markedly enriched into plant hormone signal transduction pathway. Consistently, it has been reported that auxin [74,75], cytokinins [76,77], ethylene [75,[78][79][80], gibberellin [81], abscisic acid [75,82,83], brassinosteroids [80], salicylic acid [75,78,84], jasmonic acid [75,78,[84][85][86], strigolactones [87] can actively participate in disease response. Among them, salicylic acid signal transduction and jasmonic acid/ethylene signal transduction are considered as the most common plant hormone signal transduction pathways in response to biological or abiotic stress.…”
Section: Discussionsupporting
confidence: 56%
“…Although GWAS have contributed to find high-resolution QTL and many candidate genes have been proposed for those QTL, so far, only one gene implicated in resistance to FER have been cloned: the gene ZmAuxRP1 , which encodes a plastid stroma-localized auxin-regulated protein [ 78 ]. This gene was confirmed as the causal gene of a QTL for resistance to stalk rot by F. graminearum and has shown a quick response to pathogen challenge with a rapid yet transient diminution in expression that led to arrested root growth but enhanced resistance to Gibberella stalk rot and FER.…”
Section: Genome-wide Association Studies For Fer and Fumonisin Conmentioning
confidence: 99%
“…oryzicola disease progression (Ding et al, 2008; Fu et al, 2011). Exogenous application of naphthaleneacetic acid (NAA) increases maize vulnerability to F. graminearum infection and indirectly suppresses plant immunity by reducing the levels of SA and JA (Ye et al, 2019). Arabidopsis mutant axr2‐1, which is insensitive to auxin, displays a 10‐fold reduction in P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%